1855 Ind. Acts 153, § 2 - (:unkn) unknown (My University, 1855)
ch. 79, § 2 : Prohibited shooting at or throwing projectiles at any locomotive, car, or train of cars containing people. Includes the use of guns, pistols, other weapons, or throwing stones, sticks, clubs or "any other substance whatever." Violators guilty of a misdemeanor and fined not less than ten nor more than one hundred dollars and imprisoned not less than ten days nor more than three months.
Keywords: DISCHARGE